Model Latihan Teknik Tendangan Mawashi Geri pada Olahraga Katare - Yunus, Irfan; Hudain, Muh. Adnan; Dos Santos, Hezron Ahlim; Sudirman, Sudirman (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study aims to determine the effectiveness of the use of mawashi geri practice model on karate sports. This study employs a quantitative approach using a Research and Development (R&D) methodology. The subjects in this study are 60 karateka from the Inkanas dojo in Makassar City. The small group trial consists of 30 participants, the large group trial consists of 40 participants, and the effectiveness test involves 60 participants. The research instrument is divided into three assessment criteria: initial movement, execution movement, and final movement. Data collection techniques are conducted through observation. The data analysis technique uses the